A GEP model for energy and exergy analysis of LiCl–H2O absorption cooling systems. Issue 17 (2nd September 2021) - Şencan Şahin, Arzu; Kovacı, Tuğba; Dikmen, Erkan
ABSTRACT: Absorption cooling systems use heat energy to generate chilled water rather than electrical energy that is used in vapor compression cycle. Energy and exergy analysis of absorption cooling systems is fairly complex. These analyses required a lot of time and effort. In this study, a new approach using gene expression programming (GEP) to determine coefficient of performance (COP) and exergy efficiency of the LiCl–H2 O absorption system was used. First, COP and exergy efficiency values of the LiCl–H2 O absorption system values by using EES software were calculated. Obtained values with EES software were used as datasheet for GEP model. New formulations were presented for the determination of the COP and exergy efficiency values of the LiCl–H2 O absorption cooling system. It was found that the results of the GEP model are in agreement with actual values obtained with the EES software. GEP model will be useful for determining the COP and exergy efficiency of absorption cooling systems in a shorter time and at appropriate accuracy.